2022
DOI: 10.31234/osf.io/yu7e5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Uncovering the Cognitive Mechanisms Underlying the Gaze Cueing Effect

Abstract: The gaze cueing effect is the tendency for people to respond faster to targets appearing at locations gazed-at by others compared to locations gazed away from by others. However, although the gaze cueing effect has been studied extensively and has implications for a variety of theoretical and clinical contexts, much is still unknown about the cognitive mechanisms underlying its emergence. Formal evidence accumulation models provide the dominant account of the cognitive processes underlying speeded decisions, h… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 106 publications
0
2
0
Order By: Relevance
“…Importantly, the analysis of SSP parameters show significant evidence for a faster preconscious perceptual encoding speed (ter) and a more caution decision criterion (a) as well as a stronger automatic activation (sd0) and/or a weaker suppression (sdr) in gaze judgment compared to arrow judgment. While non-decision time (ter) is generally thought to represent perceptual encoding of cues and motor preparation for decision (White et al, 2018), some studies have suggested that the effects for arrow and gaze stimuli seen here might reflect an advantage in preconscious perceptual encoding (Alister, McKay, Sewell, & Evans, 2022;Besner et al, 2021;Vainio et al 2014). Consequently, the finding that arrow judgment is more automatic than gaze judgment is not surprising since the perceptual encoding speed of arrow is faster than that of gaze.…”
Section: Discussionmentioning
confidence: 66%
“…Importantly, the analysis of SSP parameters show significant evidence for a faster preconscious perceptual encoding speed (ter) and a more caution decision criterion (a) as well as a stronger automatic activation (sd0) and/or a weaker suppression (sdr) in gaze judgment compared to arrow judgment. While non-decision time (ter) is generally thought to represent perceptual encoding of cues and motor preparation for decision (White et al, 2018), some studies have suggested that the effects for arrow and gaze stimuli seen here might reflect an advantage in preconscious perceptual encoding (Alister, McKay, Sewell, & Evans, 2022;Besner et al, 2021;Vainio et al 2014). Consequently, the finding that arrow judgment is more automatic than gaze judgment is not surprising since the perceptual encoding speed of arrow is faster than that of gaze.…”
Section: Discussionmentioning
confidence: 66%
“…In a recent application of this approach to individual differences in the gaze and arrow cueing effects, a model comparison approach revealed that while the gaze cueing effect was often characterised by a difference in nondecision time for most individuals, this was not the case for all individuals. There was a small subset of participants whose gaze-cueing effect was best characterised as a difference in start point (Alister et al, 2022). Importantly, these results highlight how the same pattern of accuracy and/or reaction times in a task may not necessarily represent the operation of the same cognitive process for all individuals.…”
Section: Individual Difference Approachmentioning
confidence: 82%
“…In a recent application of this approach to individual differences in the gaze- and arrow-cueing effects, a model comparison approach revealed that while the gaze-cueing effect was often characterised by a difference in non-decision time for most individuals, this was not the case for all individuals. There was a small subset of participants whose gaze-cueing effect was best characterised as a difference in start point ( Alister et al, 2022 ). Importantly, these results highlight how the same pattern of accuracy and/or RTs in a task may not necessarily represent the operation of the same cognitive process for all individuals.…”
Section: How Can the Study Of Social Cognition Benefit From Evidence ...mentioning
confidence: 99%